Inovasi Buku Ajar Kimia SMA/MA Kelas XI Semester Ganjil Terinternalisasi Nilai-Nilai Karakter Siswa - Riska Ritonga; Ajat Sudrajat; Eddiyanto Eddiyanto (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. This study aims to determine: (1) Test the feasibility of High School Class XI textbook commercially complies with the standards BSNP; (2) Test the feasibility of textbook by validators to high school chemistry textbook/ MA first semester of classes XI developed in accordance with the standards BSNP; (3) Test the feasibility of textbook by validators to high school chemistry textbook/ MA Class XI the first semester have developed internalized the values of the character of the students; (4) Test the feasibility of textbook by students of the high school chemistry textbook/ MA class XI semester of internalized character values of students; (5) Improved student learning outcomes after studying with a high school chemistry textbook/ MA class XI semester of internalized character values of students; (6) The results of studying chemistry student using high school chemistry textbook / MA class XI semester of internalized character values of students better than the minimum completeness criteria. The entire sample was selected by purposive sampling. Samples were determined in this study are (1) high school chemistry book/ MA Class XI outstanding as much as four books; (2) Teachers chemistry with the criteria of formal education bachelor and experienced teaching in schools as many as 10 people, chemistry lecturer criteria have minimal formal education postgraduate were 3 people; (3) A Class XI Sains-treated using a textbook teaching high school chemistry/ MA class XI half of Odd internalized character values of students based on curriculum 2013. Based on test data analysis, the results showed that (1) Test the feasibility of commercially textbooks valid criteria and should be revised; (2) Test the feasibility of the validator against chemical textbook produced in this study meet the standards required by the National Education Standards. (2) and (3) test the feasibility of the validator and students to the textbook internalized character values of students in this study meet the standard of assessment rubrics character values developed. (4) Improved student learning outcomes using chemistry textbook produced in this study is of 0.69 which is average. (5) Based on data obtained learning outcomes sign value <0.05 (0.011 <0.05) the use of high school chemistry textbook/ MA class XI half of Odd internalized the values of the student's character better than the the minimum completeness criteria.Keywords: Buku ajar kimia, terinternalisasi nilai-nilai karakter siswa